Peranan Konseling Kelompok Islam Untuk Mengurangi Perilaku Ghasab - Inayah Ayu Ningtyas; Suryati Suryati; Lena Marianti (Journal of Society Counseling, 2023)
This research is entitled "The Role of Islamic Counseling to Reduce Ghasab Behavior in Female Students at An-Nur Tebing Suluh Islamic Boarding School". Where ghasab is an act of taking or using an object that is not his right without the permission of the owner. Ghasab is different from stealing, because the perpetrator does not intend to make the item he is wearing his property. Ghasab behavior, if allowed to become entrenched, will become the forerunner of corrupt behavior, because it starts with stuttering about normal negative behavior over small things. This study aims to find out the description of ghasab behavior in female students before carrying out Islamic group counseling to reduce ghasab behavior in female students and to find out the description of ghasab behavior in female students after carrying out Islamic group counseling. The location of this research is at the An-Nur Tebing Suluh Islamic Boarding School, Lempuing District, Ogan Komering Ilir Regency. This study uses a qualitative descriptive research method. There were 5 subjects in this study, namely DNA, AH, TSP, AD and MRP. The data collection techniques used were observation, interviews and documentation while the data analysis techniques used were data reduction, data presentation, drawing conclusions and verification. The results of this study prior to the implementation of the Islamic group counseling process showed that students still often borrow items without permission, use other people's items without permission and take advantage of items without the owner's permission. Factors for students to perform ghasab include social factors (weak awareness), environmental factors (interaction that is too close), and situational factors. Then there was a change in the five subjects, namely the students already had their own items and did not use the belongings of their friends anymore, the students were subject to ghasab behavior and did not carry out ghasab behavior and there was a change in the behavior of students who initially used items without permission now to get permission first when they want to use them. other people's stuff.